Usage of Fungi in Hexadecane Tolerance - Lim, Bi Fang Vivian (2017)
Abundantly used of hexadecane in the production of fuel oil has led to the accumulation of the pollutant in soil and water which result in serious impacts on human health. In order to overcome this problem, mycoremediation approach has become the choice to remove hexadecane from polluted environment. Mycoremediation provides effective clearance of hexadecane using fungi and it was cost effective. This main objective of this study is to determine the ability of different species of fungi tolerating hexadecane by using BHB medium which carbon source was absence. Fungi species namely Apergillus nidulas, Mucor sp, Aspergillus niger, Trichoderma sp and Candida sp had been screened out as the potential fungi in tolerating hexadecane . Then the screened out fungi were proceed to test on their ability in hexadecane tolerance by measuring their dry weight. The higher the dry weight obtained, the higher the potential to be hexadecane tolerance fungi. Mucor sp (0.011 g) showed the highest towards hexadecane, followed by the Trichoderma (0.007 g). Candida species (0.005 g) showed everage tolerant capability to hexadecane . However Aspergillus genre such as Aspergillus niger (0.001 g) showed lower tolerance ability in comparison with the screened out potential fungi on hexadecane. Therefor in this experiment, Mucor sp. was found to be most potential species to be used in mycromediation for hexadecane when compared to others tested fungi.